CNS myelin structural modification induced in vitro by phospholipases A2 - Yunes Quartino, Pablo Javier (2016)
Myelin is the self-stacked membrane surrounding axons; it is also the target of several pathological and/or neurodegenerative processes like multiple sclerosis. These processes involve, among others, the hydrolytic attack by phospholipases. In this work we describe the changes in isolated myelin structure after treatment with several secreted PLA2 (sPLA2), by using small angle x-ray scattering (SAXS) measurements. It was observed that myelin treated with all the tested sPLA2s (from cobra and bee venoms and from pig pancreas) preserved the lamellar structure but displayed an enlarged separation between membranes in certain zones. Additionally, the peak due to membrane asymmetry was clearly enhanced. The coherence length was also lower than the non-treated myelin, indicating increased disorder. These SAXS results were complemented by Langmuir film experiments to follow myelin monolayer hydrolysis at the air/water interface by a decrease in electric surface potential at different surface pressures. All enzymes produced hydrolysis with no major qualitative difference between the isoforms tested.